The contamination of the soul: Plato on evil - Mavrogiannis, M (2022)
In this essay I want to explore the concept of evil in the sense of badness within Plato. I suggest that Plato had a theory of evil, and I will articulate and discuss its main features. Plato can be shown to have had a theory of evil in the sense that he had a coherent view about the nature of evil, how it is possible for things to be evil, and how these ideas fit together to explain the nature of more specific forms of evil such as, say, vice. I argue that Plato’s theory of evil is a very early version of the so-called privation theory of evil, according to which evil is the absence in a thing of what ought to be there given the essence it has as the kind of thing it is. The discussion will focus upon Plato’s doctrine of due measure as found in, among other places, Statesman, Timaeus, and Philebus.